Asking how to fish vs. asking for fish: Antecedents and outcomes of different types of help‐seeking at work. Issue 3 (14th September 2021) - Liu, Yihao; Chen, Fan Xuan; Chiang, Jack Ting‐Ju; Wang, Zheng; Liu, Haiyang
Abstract: In the modern workplace, it is virtually impossible to succeed without seeking any help from others. Despite its widely recognized importance, several areas surrounding help‐seeking have not yet been clearly understood in the organization literature. Specifically, it is unclear whether seeking help always benefits employees in need, and how various work demands drive help‐seeking behavior in different ways. In this research, we drew from the dual‐type view of help‐seeking (i.e., autonomous and dependent help‐seeking) and the challenge‐hindrance stressors framework to elaborate how seeking help of different types influences employees' work competence‐related outcomes in various directions, what work demands drive employees to seek different types of help, and when encountering work demands is particularly influential on their help‐seeking tendencies. Evidence from a field study (Study 1) showed that while challenge stressors increased employees' autonomous help‐seeking, hindrance stressors increased dependent help‐seeking especially for employees with greater workflow centrality. Moreover, autonomous help‐seeking benefited help‐seekers' job performance ratings through increased self‐perceived competence, whereas dependent help‐seeking hurt their job performance via decreased perceived competence by coworkers. To cross‐validate our findings, we then examined and replicated our core findings with three experimental vignette studies (Studies 2, 3a, and 3b). Theoretical and practical implications are discussed.